Combining the characteristics of sustainability, frugal innovations and washing machines in the industrial nations – A literature-based analysis of the common features for future sustainable developments - Schneider, Sandra (Journal of Economic Development, Environment and People, 2020)
Sustainability is an internationally discussed topic in the development of products and services. Frugal innovations aim to conserve resources in the manufacture and use of such products and services. It can therefore be assumed that the areas of sustainability and frugal innovation overlap. This work is intended to show the connection between sustainability, frugal innovations and household appliances in the form of washing machines in industrialized countries. For the analysis, the characteristics of frugal innovations are compared with the requirements of washing machines in industrial nations and then the parallels to the social development goals (SDG) are determined as characteristics for sustainability. The existing literature will be reviewed for evaluation. The aim of the work is to show the connection and give an indication of the sustainable development of an everyday product as a frugal innovation in the industrialized countries.